Effect of treatment period on apus bamboo on compressive strength and Young's modulus: Efek masa perawatan pada bambu apus terhadap kuat tekan dan modulus young - Salva Achmad Lail; Dian Purnmawati Solin (LPPM Universitas Abdurrab, 2025)
As time goes by, land is getting narrower and the price of land to build a building is getting higher. It is often found in the field that soil conditions are less favorable, especially on soft soil. So, there is a need for soil improvement measures to overcome this problem but at a relatively low cost. Using bamboo as soil reinforcement is a soil improvement technique that is easy to apply, can save costs, and has been proven safe to use several times in previous research. Apart from that, bamboo populations are also easy to find in almost all regions of Indonesia. In previous research, soil improvement was rarely carried out using Apus type bamboo as soft soil reinforcement. This is due to the lack of previous research on the compressive strength and young modulus values ​​of Apus type bamboo. Therefore, this research was carried out with the hope of providing an overview of the results of the compressive strength and Young's modulus values ​​of Apus type bamboo. The method used in testing was carried out by testing the compressive strength and young modulus values ​​of Apus type bamboo which were differentiated based on different treatment durations. Based on the test results, Apus bamboo without treatment has a compressive strength of 38.50 Mpa, where the more the bamboo is treated, the higher the compressive strength results obtained and the greatest value is obtained by bamboo with a treatment period of 14 days, namely 44.49 Mpa. Meanwhile, the elastic modulus value for bamboo for 7 days was 160847.187 kN/m2 and for treatment for 14 days the value was 287556.583 kN/m2.